Pengolahan Limbah Botol Infus Dengan Prinsip Daur Ulang (Studi Kasus: Rumah Sakit Kota Bekasi) - Aanisah Ayu Dwi Safitri; Gina Lova Sari; Venny Ulya Bunga (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Infusion bottles are one of the largest types of medical waste found in hospitals, reaching 4,732 kg in 2023. Infusion bottle waste is classified as infectious hazardous waste and requires proper handling. One alternative is to use the recycling principle to minimise the generation of infusion bottle waste. This research aims to investigate the potential for reducing infusion bottle waste in hospitals. The research was conducted by determining the generation of infusion bottle waste according to the method in SNI 19-3964-1994. The recycling of infusion bottle waste was carried out through several stages, including emptying, cleaning, disinfecting and drying, and crushing or shredding the infusion bottle waste. The results showed that the amount of IV bottle waste generated in one hospital in Bekasi City was 3.66 kg/day. The potential for disinfection can be achieved by sterilisation using chlorine solution (0.50%) and alcohol (0.70%). With a soaking time of 10 minutes, further utilisation of sterile infusion bottle waste was carried out by shredding the particles into 8.00 - 15.00 mm. The method used in this recycling process can minimise infusion bottle waste by 9.01%.